Online monitoring and self-tuning control using pole placement method for active vibration control of a flexible beam. (February 2015) - Saad, Mohd Sazli; Jamaluddin, Hishamuddin; Mat Darus, Intan Zaurah
This paper presents the experimental results of online self-tuning pole placement control for active vibration of a flexible beam. The vibration is controlled using a piezoelectric actuator bonded on a flexible beam. An online computer control that runs on a PC-based control and its graphical user interface have been developed in such a way that the user can perform online monitoring and manipulation of control parameters of the active vibration control algorithm for a flexible beam system. The parameters of the pole placement controller have been self-tuned based on autoregression with an exogenous terms model of a bonded piezoelectric actuator beam identified via a recursive least square algorithm. A PC-based control system was implemented using a peripheral component interconnect data acquisition card and LABVIEW software. Results show that the online self-tuning pole placement control offers better transient performance over the fixed controller when tested at different tip loads. The control parameters have converged to a new value as the physical parameter of a flexible beam is changed.